Auditoria a la cuenta de inventarios de insumos agrícolas y su relación con la rentabilidad en la hacienda zulay del cantón Valencia periodo 20122 - Cedeño Vera, Vanessa Alejandra (2013)
Today companies looking banana production tools to help improve inventory control minimizing production costs and implement a control system in the inventory accounts for the purpose of obtaining information necessary for good decision making and better performance. This research aims to " Perform an audit of the inventory account of agricultural inputs and their relationship to profitability in Zulay hacienda Canton Valencia " in 2012 , proceeded to conduct a comprehensive audit department inventories to identify shortcomings in terms the purchase and distribution of agricultural inputs determine a report to measure the profitability of the farm. Field research was conducted by interviewing techniques, questionnaire and observation which served them a lot to understand the context of the department inventory and determine the need for a control system inventory accounts. Some methods like the Analytic that involves removing part a whole in order to study and examine the inventory account, deductive method to use reasoning to draw conclusions from the data analysis of stocks inventory was used and Inductive method through this method a general market analysis of banana exports, place and confirm the existence of unmet potential customers into buyers of bananas. This three methodology is the main foundation for the development of our audit, because by this method may determine as an audit of the Treasury profited Zulay links.